Shakespeare in the undiscovered bourn : Les Kurbas, Ukrainian modernism, and early Soviet cultural politics - Makaryk, Irene Rima (University of Toronto Press, 2004)
"Les Kurbas - director, actor, playwright, filmmaker, and translator - was the first artist to introduce Shakespeare to the Ukranian stage. Creating the foundations of Soviet Ukranian theatre and cinema, he was also responsible for its avant-garde direction. Shakespeare in the Undiscovered Bourn is the first book-length study in English of Kurbas's modernist productions of Shakespeare and the first book on Soviet Shakespeare productions in Ukraine in any language."--Jacket